What literature does to our emotions, and how do we know? Empirical studies will tell - Willie van Peer; Anna Chesnokova (Синопсис: текст, контекст, медіа, 2019)
The general feeling of malaise, if not crisis, in Literary Studies forces us to urgently look for solutions that will bring the discipline forward. This article is a call for a concentration on fundamental issues in the study of literature, and at the same time for a more rigorous and accountable methodology in studying both the content and the form of literary texts as well as readers’ reactions to them. Some illustrations of work in the area of Empirical Study of Literature are provided, showing how fiction is a powerful regulator of human emotion, especially by formal features of the text. Case 1 reports a study which looks at the influence of narrative perspective (internal focalization in the first place) on judgements of readers. Case 2 delves into the textual ingredients by which readers’ absorption in a narrative world is enhanced. These ingredients are foremost of a kind that goes under the name of “foregrounding” devices in literary studies. The conclusion from the research is that texts that are rich in foregrounding are better able to elicit a more complex response, i.e., a more powerful impact, from readers. In its turn Case 3 looks at how readers react to literary pieces dealing with deep human suffering. The findings indicate that literature is able to evoke strong feelings of empathy through its formal make-up. The results also support the argument that one’s exposure to literature is the main variable to have an impact on prosocial behaviour, irrespective of personality, gender, age or social situation. Thus we claim that literary texts exert a powerful influence on readers’ value sharing, absorption and empathy, and the impact can only be studied empirically. The article shows a way out of the current crisis, not by just opening up a new fashion, in which literary texts are “interpreted” in yet another way, mostly academically, but by taking literary texts seriously in their workings on the minds and hearts of readers — which is ultimately what texts are written for.